Trading Houses during and since the Great Commodity Boom: Financialization, productivization or…? - Peter Gibbon (Danish Institute for International Studies (DIIS), 2014)
The largest Commodity Trading Houses account for a large and increasing share of international trade, linked arguably to their financialization and - according to some commentators - giving rise to issues of 'systemic importance' similar to those applying to large investment banks. This paper evaluates the extent of Commodity Trading House financialization during the period 2004- 13 looking at the top 10 trading houses through the lens of five indicators: relations to capital markets; leverage; asset composition; structure of corporate activities and returns; and types of merger and acquisition activity. Its tentative conclusions are that, while listed trading houses along with Cargill exhibit financialization across most indicators, financialization is a weaker and more diffuse trend for the majority of the top 10, which remain in private ownership. Moreover, financialization indicators peak around 2008 and seemingly decline during the second half of the period.
Keywords: 330; Commodities; Commodity markets; Trading Houses; Financialization; Financial markets